Kemampuan Hasil Belajar dan Berpikir Kritis Siswa dengan Menggunakan Model Pembelajaran Inkuiri Melalui Google Classroom - Aprianti Suhidi; Rusdi Hasan; Tomi Hidayat (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2021)
This study aims to determine the differences in the ability of students' learning outcomes and critical thinking using the Inquiry learning model through Google Classroom at SMA Negeri 9 Bengkulu City. The method used is Quasi Experiment. The results showed that learning outcomes and students' critical thinking skills in Inquiry learning with Google Classroom media at SMA N 9 Bengkulu City obtained a significance value of 0.000. In conclusion, students who receive learning using an inquiry model through Google Classroom have better learning outcomes and critical thinking skills than students who receive learning using conventional methods. Keywords: Critical Thinking, Learning Outcomes, Inquiry